Combustion physics - Law, Chung K., 1947- (Cambridge University Press, 2006)
This is a graduate-level text on the fundamentals of chemically reacting flows, intended for students and researchers in a variety of applied sciences and engineering. It is especially relevant to work in heat and power generation, burners and internal combustion engines, energy conservation, aero-propulsion, petroleum fuels and alternate fuels, pollution control, and fire and explosion hazards.